ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA TERHADAP MATERI MUNAKAHAT PADA PEMBELAJARAN FIQIH - Mafruhah, Ane Zunnatul; Afifah, Yanti Amalia; Hasbiyallah, Hasbiyallah; Farida, Ida (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
Fiqih is one of the essential subjects at the Madrasah Aliyah level because it provides an understanding of Islamic Shari'a law.Law is dynamic, therefore, to understand Islamic law, critical and creative thinking is needed. This is due to the growing era and the ever-changing problems of life. The industrial revolution 4.0 is a 21st century world development that demands changes in competence, which is marked by the use of information and communication technology in all aspects of life, including in the learning process. The ability to think critically, solve problems, and collaborate is an important competency in entering the life of the 21st century, requiring the government to improve human resources. Likewise in the world of education, students must be able to solve problems with their critical thinking skills. This study aims to analyze the critical thinking skills of class XI students in one of the madrasah aliyah in the city of Bandung. The method used in this research is descriptive quantitative using a test as a research instrument. The results of processing and analysis of this study indicate that students' critical thinking skills are in the moderate category with an average score of 73. Therefore, in the learning process, teachers must always improve the quality of education by facilitating students to develop their critical thinking skills and abilities.